Pengaruh Pengendalian Internal dan Budaya Etis Organisasi Terhadap Kecenderungan Kecurangan (Fraud) Akuntansi - Ida Bagus Putu Narayana; I Wayan Sudiana; Ni Made Wisni Arie Pramuki (UNHI Press, 2023)
This study was made to determine the relationship of variables that can affect the tendency of fraud. Those variables are internal control and ets culture in the organization. cooperatives as a whole that are still active in Gianyar district were chosen to be the research sites. The sample of this study amounted to 81 people where the data will be collected later by the process of distributing questionnaires. SEM PLS was used as an analytical method in this study. In this study it was found that the level of accounting fraud can be reduced by improving the internal control system and coupled with an organizational ethical culture that is well implemented in the company.